Consumer’s Knowledge, Attitude, and Practices toward Self-medication: Questionnaire Development and Validation - Nahid Ansari; Abhishek Dadhich (Archives of Medicine and Health Sciences)
Background and Aim: Self-medication practices (SMPs) are a common phenomenon prevalent with both prescription and nonprescription medicines. Still, the availability of a valid and reliable instrument to assess the knowledge, attitude, and practices toward self-medication (SM) remains limited. The current pilot study aimed to develop and validate a tool that effectively evaluates these aspects among consumers in Delhi, India. Materials and Methods: The research involved 100 consumer participants from Delhi, India. Reliability and validity testing was conducted to assess reproducibility, internal consistency, and content validity. The questionnaire underwent validation by a panel of five experts to evaluate face and content validity. Results: Test–retest reliability was assessed using Karl Pearson’s correlation co-efficient yielding values of 0.841 (P = 0.002), 0.827 (P = 0.003), and 0.792 (P = 0.006) for the three domains of knowledge, attitude, and frequency of performing SM, respectively. Cronbach’s alpha statistics were used to determine internal consistency, yielding values of 0.775 and 0.839 for knowledge and attitude domains, respectively. The association between the demographic characteristics of respondents and knowledge, attitude, and frequency of SM was assessed using an independent sample t-test and one-way ANOVA, demonstrating satisfactory known group validity. Conclusions: The developed questionnaire proved valid and reliable for determining consumer’s knowledge, attitudes, and practices toward SM. The final tool could be valuable for future research and interventions to improve consumers’ understanding of SMP.